Implementation of Diversion in the Juvenile Justice System at Kendari District Court - Iksan, La Ode Muh; Rifai, A; Dagani, Gamlang; Wahyuddin, Wahyuddin (Al-'Adl, 2025)
This research discusses the application of diversion in the juvenile justice system in the KendarI prosecutor's office This research uses normative legal research methods, namely by examining library materials which are secondary data. In this case normative legal research is research conducted with a focus on positive law in the form of legislation. The data used is secondary data from primary legal materials and secondary law. The research used is descriptive analysis, with a normative juridical approach in the legal references used referring to primary law and secondary legal materials, namely Law number 11 of 2012. About the juvenile justice system and related legislation. The results of the research used are qualitative descriptive research. The application of Diversion in the Juvenile Criminal Justice System at the Kendari District Court has been successfully carried out in juvenile criminal cases with sharp weapons / fire cases by going through the preparation stage, the judge's determination stage, the consultation stage, the agreement stage carried out by peaceful means between the two parties without any compensation. Diversion which is peaceful without loss by referring to the resolution of conflicts between children in conflict with the law through processes outside the criminal justice system, with the aim of achieving peace without causing harm to all parties, especially children and victims.